128k views
2 votes
Drag each equation to show if it could be a correct first step to solving the equation 3(6 + x) = 24.

User Soley
by
6.0k points

2 Answers

6 votes

Answer:

(3×6) + (3×x) = 24 ← 1st Step

Explanation:

3(6+x) = 24

First step is expand the brackets by distributive property.

=> (3×6) + (3×x) = 24 ← 1st Step

Multiply

=> 18+3x = 24 ← 2nd Step

Subtracting 18 to both sides

=> 3x = 6 ← 3rd Step

Dividing both sides by 3

=> x = 2 ← 4th step

User Steve Rowe
by
5.6k points
0 votes

Answer:

x = 2

Explanation:

Step 1: Distribute

18 + 3x = 24

Step 2: Subtract 18 from both sides

3x = 6

Step 3: Divide both sides by 3

x = 2

Your first step would be to distribute/multiply the 3 to the parenthesis.

User Raystafarian
by
4.8k points